Analisis Investasi Aplikasi Trading Binomo: Studi Kasus Indra Kenz - Annisa Radila Tarigan; Dea Ratna Sari Siregar,; Fauziah Lubis (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
The crime of money laundering under the guise of investment is very important to be discussed, discussed, and analyzed because now this crime is getting easier to do. One reason is globalization. What is the OJK's steps in the case that is currently happening in the community? How does the Binomo app work? Data collection is done by analyzing from several sources of books and journals, which in this case explains the steps of the OJK as the role of the Financial Supervisory Agency in Indonesia. OJK is a financial supervisory agency with the aim that all financial service activities in the financial services sector are carried out in an orderly, fair, transparent, and accountable manner, considering the currently busy case, namely the crime of money laundering under the guise of investment committed by Indra Kenz. Keywords: Financial Services Authority, Binomo, Indra Kenz